Effects of Fish Meal Replacement with Full-Fat Soy Meal on Growth and Tissue Fatty Acid Composition in Atlantic Cod (Gadus morhua) - Karalazos, Vasileios; Treasurer, Jim; Cutts, Christopher J; Alderson, Richard; Galloway, Trine F; Albrektsen, Sissel; Arnason, Jon; MacDonald, Niall; Bell, J Gordon (Journal of Agricultural and Food Chemistry, 2007)
Atlantic cod of initial mean weight ~220g were fed a control diet and three diets where fish meal (FM) was replaced with increasing levels of full fat soybean meal (FFS) supplied at 12, 24 and 36% of dry diet, for 12 weeks. There were no significant differences in final weights but the specific growth rate (SGR) was significantly higher in fish fed the control (FFS0) diet compared to fish fed the FFS12 and FFS36 diets and the feed conversion ratio (FCR) was significantly lower in fish fed the FFS0 diet compared to the other three treatments. The fatty acid (FA) compositions of the cod muscle and liver were highly affected by dietary treatment and linear relationships between dietary and tissue FA concentrations were shown for some of these. Moreover, selective utilization or accumulation in the tissues of specific FA was suggested by the results.